2016
DOI: 10.3233/bmr-160720
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain in Parkinson's disease: Frequency, characteristics, independent factors, and relationship with health-related quality of life

Abstract: This study demonstrated that chronic pain is a common problem in patients with PD, that different pain types may co-exist, and that they may negatively affect the HRQoL of patients. Chronic pain was correlated with both disease-related factors such as rigidity and daily living activities and also general factors such as gender and depression. We found that chronic pain is the most significant predictor of quality of life in PD patients. We believe, that in addition to treating motor symptoms and complications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
2
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 37 publications
1
25
2
4
Order By: Relevance
“…This might suggest that in the FJ group, there is a bidirectional relationship between anxiety/depression and myoclonus. Previous studies have shown that chronic pain negatively influences mood and quality of life [22]. However, in our cohort pain did not explain the relationship between anxiety/depression and myoclonus, as pain was not correlated to myoclonus severity.…”
Section: Accepted Manuscriptcontrasting
confidence: 91%
“…This might suggest that in the FJ group, there is a bidirectional relationship between anxiety/depression and myoclonus. Previous studies have shown that chronic pain negatively influences mood and quality of life [22]. However, in our cohort pain did not explain the relationship between anxiety/depression and myoclonus, as pain was not correlated to myoclonus severity.…”
Section: Accepted Manuscriptcontrasting
confidence: 91%
“…On the other hand, using the King's Parkinson's Disease Pain Scale (KPPS), the syndromic nature of pain has been formally subdivided into several patterns. Prior research has shown that the prevalence of pain is 68 to 81% in PD patients and that it can be manifested in several modalities, such as musculoskeletal (41–89%), dystonic (15–17%), radicular‐neuropathic (27–32%), and central pain (4–22%) . Furthermore, 35% of PD patients are affected by two types of pain, 10% by three, and 2% by four .…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has shown that the prevalence of pain is 68 to 81% in PD patients [12][13][14] and that it can be manifested in several modalities, such as musculoskeletal (41-89%), dystonic (15-17%), radicular-neuropathic (27-32%), and central pain (4-22%). 2,12,[14][15][16][17][18] Furthermore, 35% of PD patients are affected by two types of pain, 10% by three, and 2% by four. 14 Pain can become crippling in a subset of PD patients, affect their ability to conduct activities of daily living (ADL), 13,19 and negatively impact their QoL.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic pain is a highly prominent symptom in people with Parkinson's disease (PwPD), yet there is a limited understanding of whether the pain is primarily a consequence of motor impairment, including muscle rigidity, or whether Parkinson's disease (PD) causes a centrally produced heightened sensitivity to pain. Whilst the percentage of the general population living with chronic pain is approximately 20% (Breivik, Collett, Ventafridda, Cohen, & Gallacher, ; van Hecke, Torrance, & Smith, ), there is a significantly higher prevalence within the PD population of approximately two‐thirds (Nègre‐Pagès, Regragui, Bouhassira, Grandjean, & Rascol, ; Ozturk, Gundogdu, Kocer, Comoglu, & Cakci, ; Silverdale et al., ; Skogar & Lokk, ). There is evidence that PwPD have lower threshold and tolerance of pain compared to age‐matched healthy cohorts (Brefel‐Courbon et al., ; Chaudhuri & Schapira, ; Djaldetti et al., ; Schestatsky et al., ), and EEG and functional imaging studies have demonstrated an altered central response to pain in PD (Brefel‐Courbon et al., ; Schestatsky et al., ; Tinazzi et al., ).…”
Section: Introductionmentioning
confidence: 99%